Rol educativo del personal de enfermería y su relación con la prevención de embarazos en las adolescentes de la unidad educativa Babahoyo, Los Ríos, Babahoyo periodo mayo- septiembre del 2019 - Campuzano Amat, Ambar Marlene (2019)
Introduction. The adolescent pregnancy prevention is now an imperative by the high rates in Latin America. In Ecuador, the fertility rates are very high (second in the region), more evident in children under 15. General objective. To determine the relationship between the educational role of nurses and the prevention of pregnancies in adolescents in the educational unit Babahoyo, of canton Babahoyo, Los Ríos province during the period from May to September 2019. Methodology. Research was based on methods to theoretical and empirical level, employed the quali-quantitative mode, depending on its purpose, was field, taking into account the level of study, was exploratory and descriptive, the purpose was not experimental, and applied according to the dimension temporary, was cross. Data collection techniques used were not structured and direct scientific observation as well as survey, a questionnaire as an instrument. The sample and the universe was 250 and 95 teenage respectively, used sampling non-probability intentional. Results. The age group of adolescents with higher prevalence was understood from 10 to 14 years old, followed by the 15 to 19 years old. Conclusions. The main risk factors for pregnancy in adolescence are the early onset of sexual relations, lack of knowledge of the methods of family planning, insufficient family and school guidance on sexuality and zero training education of nurses on these issues.